Kangaroo Island propolis types originating from two Lepidosperma species and Dodonaea humilis. (August 2021) - King, Douglas I.; Hamid, Kaiser; Tran, Van H.; Duke, Rujee K.; Duke, Colin C.
Abstract: The endemic Australian plants Lepidosperma sp. Flinders Chase (Cyperaceae), Lepidosperma viscidum (Cyperaceae) and Dodonaea humilis (Sapindaceae) were found to be the botanical origin of three propolis types found on Kangaroo Island identified by TLC and 1 H NMR matching of propolis and plant resin analytical profiles. Resin samples extracted from the plant, Lepidosperma sp. Flinders Chase, were chromatographically fractionated to give: methyl 3-phenyl-2-( E -cinnamoyloxy)propanoate (1 ), 3-( E -8-methoxy-8-oxo-3, 7-dimethyloct-2-enyl)-4-hydroxy- E -cinnamic acid (2 ), 3-( E -6, 7-dihydroxy-3, 7-dimethyloct-2-enyl)-4-hydroxy- E -cinnamic acid (3 ), previously undescribed; and the known stilbenes, 2-prenyl-3, 5-dihydroxy- E -stilbene (6 ) and 2-prenyl-3-methoxy-5-hydroxy- E -stilbene (7 ). The resin from L. viscidum gave: 5′-( E -4-hydroxy-3-methylbut-2-enyl)-4, 2′, 4′-trihydroxydihydrochalcone (4 ); 5′-( E -4-hydroxy-3-methylbut-2-enyl)-4′-methoxy-4, 2′-dihydroxydihydrochalcone (5 ), previously undescribed; and three known flavanones, farrerol (8 ), 5, 7, 3′, 5′-tetrahydroxy-6, 8-dimethylflavanone (9 ) and 5, 7, 3′, 5′-tetrahydroxy-6-methylflavanone (10 ). The major constituent in the propolis identified as being sourced from D. humilis was identified as 6, 8-diprenyl-5, 7, 3′, 4′-tetrahydroxyflavanone (11 ), a known compound identified in several unrelated plant species. Graphical abstract: Two approaches for analyzing 'single source' propolis constituents: -Identify plant source of the propolis by pattern recognition of analytical profiles, then identify constituents in the plant source. Identify constituents in the propolis, then identify the plant source by pattern recognition of analytical profiles and evidence from known plant sources of the identified constituents. Image 1 Highlights: A method for finding potentially useful medicinal phytochemicals from propolis was developed. Pattern recognition of propolis analytical profiles was applied to identify source plants. Propolis plant sources identified, two Lepidosperma species and Dodonaea humilis. Three undescribed cinnamate derivatives were identified from Lepidosperma sp. Flinders Chase. Two undescribed hydroxyprenylated dihydrochalcones were identified from Lepidosperma viscidum.